PEMBERDAYAAN KADER POSBINDU DALAM DETEKSI DINI FAKTOR RISIKO PENYAKIT TIDAK MENULAR - Sri Noor Mintarsih; Zuhria Ismawanti; Kun Aristati Susiloretni; Ria Ambarwati (Jurnal Abdimas Bina Bangsa, 2023)
Non-communicable diseases (NCD) are the main cause of death in the world, 70%. NCD events such as hypertension and diabetes are expected to continue to increase. Early detection of NCD Risk Factors in the community can be done at Posbindu which is a promotive and preventive activity. The results of interviews and preliminary studies revealed that the implementation of Posbindu activities was felt to be not optimal, due to the limited number of trained cadres. Based on this, it is necessary to empower Posbindu cadres in early detection of NCD risk factors. Service method in the form of training for health cadres. Cadres are expected to be able to detect risk factors for NCD in the community so that prevention can be carried out as early as possible. The activity was carried out on 19-20 August 2022, attended by 10 health cadres from the Gabahan and Pekunden sub-districts in the working area of the Miroto Health Center. The results of the training revealed that there was an increase in cadres' knowledge about posbindu and NCD as well as the skills of cadres in checking weight, height, measuring abdominal circumference, blood pressure, checking blood sugar, cholesterol and uric acid